2021
DOI: 10.1111/ctr.14379
|View full text |Cite
|
Sign up to set email alerts
|

Valganciclovir prophylaxis extension from 3 to 6 months in high‐risk pancreas‐transplant recipients does not impact incidence of cytomegalovirus infection at 12 months

Abstract: Problem: Incidence and impact of CMV infection in pancreas-transplant recipients (PTRs) in the valganciclovir prophylaxis era has not been completely elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…While prophylaxis with VGC has improved the prevention of CMV disease, late onset CMV infection after completion of prophylaxis remains a significant issue. While a pivotal study in kidney transplant recipients suggested prophylaxis extension from 100 to 200 days reduced the incidence of late onset CMV, this benefit has not been demonstrated when extrapolated to other allograft subtypes 25 . The results of our study suggest that the liver transplant population is not spared from this problem, with a median time to CMV of approximately 5 months posttransplant, suggesting postprophylaxis onset.…”
Section: Discussioncontrasting
confidence: 50%
“…While prophylaxis with VGC has improved the prevention of CMV disease, late onset CMV infection after completion of prophylaxis remains a significant issue. While a pivotal study in kidney transplant recipients suggested prophylaxis extension from 100 to 200 days reduced the incidence of late onset CMV, this benefit has not been demonstrated when extrapolated to other allograft subtypes 25 . The results of our study suggest that the liver transplant population is not spared from this problem, with a median time to CMV of approximately 5 months posttransplant, suggesting postprophylaxis onset.…”
Section: Discussioncontrasting
confidence: 50%
“…23 However, when evaluated in other allograft subtypes extension appears to only delay the onset and does not reduce incidence. 24,25 This is thought to be due to the inability to mount CMV-specific cell-mediated immunity while receiving valganciclovir…”
Section: Discussionmentioning
confidence: 99%
“…Again, the duration of surveillance is based on literature suggesting a significant reduction in CMV disease after 1 year 20 . Center specific data in pancreas transplant recipients that demonstrated prophylaxis extension only delayed onset and did not reduce incidence of CMV further corroborated this and was the basis for our surveillance initiative 18 . Pancreas recipients are followed for an additional 6 months after prophylaxis termination.…”
Section: Background and Introductionmentioning
confidence: 94%
“…16 This is mostly attributed to symptomatic late-onset postprophylaxis CMV due to a lack of pretransplant learned immunity. While prophylaxis extension may reduce incidence in kidney transplant recipients, this has not been successfully demonstrated in other allograft subtypes 17,18 and remains an issue in kidney transplant patients with reported rates of late onset infection up to 48% despite 6 months of VGC prophylaxis. 19 However, CMV infection >1 year after transplant is uncommon, with literature reported rates of <5%.…”
Section: High Risk CMV Monitoringmentioning
confidence: 99%